Development of Science Practicum Guide Based On Collaborative Teamwork Learning (CTL) Learning Model for Students of SMPN 3 Bonjol - Rahmi, Ennike Gusti; Sudirman, Destaria; Sari, Nurhaty Purnama (Perspektif Pendidikan dan Keguruan, 2023)
Teachers at SMPN 3 Bonjol in carrying out practicum activities have not used practicum guidelines. Practicum activities carried out by teachers so far tend to only provide instructions. This is because the school does not yet have a practicum guidebook. Difficulties are also faced by students, because students do not know what practicum activities will be carried out and cause a lack of student preparation in doing practicum. This study aims to produce a valid, practical, and effective practicum guide based on Collaborative Teamwork Learning for grade VII students at SMPN 3 Bonjol. Type of Development Research (Develpomental research), The data collection techniques used are validation sheet questionnaires, practicality sheet questionnaires, affective assessment rubrics, psychomotor assessment rubrics. Data analysis techniques using descriptive statistics. Validity and practicality questionnaires are made according to Likert scales. For effectiveness is seen through learning outcomes. The overall validity test results obtained a percentage value of 85.20% with valid criteria. The results of the overall practical alias teacher test were obtained with a percentage value of 90.86% with very practical criteria. The overall student practicality test results were obtained with a percentage value of 92.65 with very practical criteria. Test the effectiveness of using the Collaborative Teamwork Learning-based science practicum guide obtained through student activities, motivation, and student learning outcomes has been produced by a science practicum guide based on Collaborative Teamwork Learning which is effectively used to improve students' understanding of concepts and science process skills..